2021
DOI: 10.3389/fphar.2021.744811
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin-Loaded Tumor-Targeting Peptide-Decorated Polypeptide Nanoparticles for Treating Primary Orthotopic Colon Cancer

Abstract: Colorectal cancer is the third most common malignant disease worldwide, and chemotherapy has been the standard treatment for colorectal cancer. However, the therapeutic effects of chemotherapy are unsatisfactory for advanced and recurrent colorectal cancers. Thus, increasing the treatment efficacy of chemotherapy in colorectal cancer is a must. In this study, doxorubicin (DOX)-loaded tumor-targeting peptide-decorated mPEG-P(Phe-co-Cys) nanoparticles were developed to treat orthotopic colon cancer in mice. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Pharmaceutics 2022, 14, x FOR PEER REVIEW differences [42,43]. Furthermore, the release behavior of Dox from different kin was found to collate to our findings.…”
Section: In Vitro Drug Releasesupporting
confidence: 75%
See 1 more Smart Citation
“…Pharmaceutics 2022, 14, x FOR PEER REVIEW differences [42,43]. Furthermore, the release behavior of Dox from different kin was found to collate to our findings.…”
Section: In Vitro Drug Releasesupporting
confidence: 75%
“…These factors were related to the release profile of Dox-NPs obtained [ 40 , 41 ]. According to the literature review on Dox delivery to colorectal cancer, similar findings were found; for example, Lui et al (2021) as well as Abedi et al (2021) reported that the release of Dox was pH dependent, where a more rapid release was found at lower pH value, regardless of the NPs’ construction differences [ 42 , 43 ]. Furthermore, the release behavior of Dox from different kinds of NPs was found to collate to our findings.…”
Section: Resultsmentioning
confidence: 55%
“…Biological therapeutics, for example, antibodies, peptide-mimetics, and a few cytokines showed target-specific effects, and they are relatively safer to be used in cancer treatment ( 5 ). Furthermore, studies also showed that engineered nanoparticles have selectivity in detecting and destroying tumour cells ( 6 9 ). However, physiological and physical limitations for incorporating engineered nanoparticles in cancer treatment still exist.…”
Section: Introductionmentioning
confidence: 99%
“…However, physiological and physical limitations for incorporating engineered nanoparticles in cancer treatment still exist. These include protein adsorption, phagocytic sequestration, diffusion, flow, and shear forces which reduce the extent of diffusion of nanoparticles to the tumour cells ( 6 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Streptomyces , as mentioned, contain anti-cancer compounds that can be used as chemotherapy drugs [ 28 ] that is often used treat to control advanced cancers to enhance survival [ 29 ]. Among these cancers that usually spread to other organs, chemotherapy is the most common treatment for CRC [ 30 , 31 ] that many lifestyle factors, obesity and dietary patterns are linked to the cancer [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%